NEW WINTER CRANE FLIES (INSECTA: DIPTERA: TRICHOCERIDAE) FROM THE JURASSIC DAOHUGOU FORMATION (INNER MONGOLIA, CHINA) AND THEIR ASSOCIATED BIOTA - Zhang J. (My University, 2006)
Four extinct new species referable, respectively, to three extinct new genera within Trichoceridae have been recovered from the Jurassic Daohugou Formation in Ningcheng, Chifeng, Inner Mongolia, China: Archaeotrichocera ephemera gen. et sp. nov., Tanyochoreta integera gen. et sp. nov., Tanyochoreta chifengica sp. nov., and Sinotrichocera parva gen. et sp. nov. The specimen described earlier as trichocerids from China, Mesotrichocera laiyangensis Hong and Wang 1990, does not belong to this family. The Daohugou biota comprises a wide range of vertebrate and invertebrate organisms that inhabited, a small take, luxurious everglade, streams, and forest with volcanoes nearby. The Daohugou Formation can be compared to the Karabastau and Haifanggou formations based on biostratigraphic correlation. The geological age for trichocerid-bearing nonmarine volcano-sedimentary rocks may be latest Middle Jurassic (Callovian) or earliest Late Jurassic (Oxfordian) rather than early-middle Middle Jurassic or Early Cretaceous. © 2006 NRC Canada.
Keywords: Cretaceous; Oxfordian; Callovian; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic::Upper::Oxfordian; Мезозой::Юрская::Верхний::Оксфордский; Mesozoic::Jurassic::Middle::Callovian; Мезозой::Юрская::Средний::Келловейский